GREENLAND WHITEOUT EXPERIMENTS: SUMMER 1960. - Jiusto,James E.; Rogers,R. R. (1960)
A two-month experimental program was conducted in Greenland to determine the extent to which arctic whiteouts and low clouds could be modified using cloud dissipation techniques. Seven seeding agents, applicable to supercooled or warmer-than freezing clouds, were tried employing aircraft, tethered blimp, and rocket delivery modes. Successful dissipation of supercooled clouds was achieved with dry ice. Seeding materials that were ineffective in dissipating the supercooled clouds or warmer-than-freezing clouds encountered were liquid carbon dioxide, Greenland soil particles, silver iodide, carbon black, calcium chloride, and sodium chloride. Cloud hydrometeor and atmospheric nuclei measurements were made in relation to the modification tests. Specialized seeding equipments for specific arctic operations are recommended.